2021
DOI: 10.17085/apm.20093
|View full text |Cite
|
Sign up to set email alerts
|

Real world adverse events of interspinous spacers using Manufacturer and User Facility Device Experience data

Abstract: Background: Lumbar spinal stenosis is a condition of progressive neurogenic claudication that can be managed with lumbar decompression surgery or less invasive interspinous process devices after failed conservative therapy. Popular interspinous process spacers include X-Stop, Vertiflex and Coflex, with X-Stop being taken off market due to its adverse events profile. Methods: A disproportionality analysis was conducted to determine whether a statistically significant signal exists in the three interspinous spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Some authors have also optimized the structure of Coflex by means of topological optimization to reduce the concentration of spinous stress and reduce the incidence of complications [29,30]. The results of our study showed that the maximum spinous stresses occurred during extension and that the maximum contact forces on the spinous process occurred at the L4 spinous process in all fixation models, with the highest in the X-Stop model, which is consistent with the clinical findings of spinous fractures reported in a systematic review [31], where up to 14 spinous fractures cases were reported in the X-Stop, significantly higher than the 5 cases in the Coflex, with the difference being statistically significant. It is possible that the spine disruption load may be reduced if under repeated loading, leading to the occurrence of spine fractures.…”
Section: Discussionsupporting
confidence: 88%
“…Some authors have also optimized the structure of Coflex by means of topological optimization to reduce the concentration of spinous stress and reduce the incidence of complications [29,30]. The results of our study showed that the maximum spinous stresses occurred during extension and that the maximum contact forces on the spinous process occurred at the L4 spinous process in all fixation models, with the highest in the X-Stop model, which is consistent with the clinical findings of spinous fractures reported in a systematic review [31], where up to 14 spinous fractures cases were reported in the X-Stop, significantly higher than the 5 cases in the Coflex, with the difference being statistically significant. It is possible that the spine disruption load may be reduced if under repeated loading, leading to the occurrence of spine fractures.…”
Section: Discussionsupporting
confidence: 88%
“…It was found that the probability of Coflex loosening is 60%. Previous research has reported Coflex loosening probability of 4.7–20.5% during long-term follow-up [ 18 21 ]. Our findings indicated a higher incidence of Coflex loosening and found no effect on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Device manufacturers and device user facilities are required to report any device malfunction and any suspected device-related serious injury or death. The MAUDE database has been used previously to describe complications associated with multiple chronic pain devices 10–15. As such, it has become an important source of real-world information to analyze large cohorts of device-related complications.…”
mentioning
confidence: 99%
“…The MAUDE database has been used previously to describe complications associated with multiple chronic pain devices. [10][11][12][13][14][15] As such, it has become an important source of real-world information to analyze large cohorts of device-related complications. It is important to note that there are limitations to utilizing the MAUDE database as it is not intended to evaluate rates of adverse events (AEs) or to perform comparative analyses across different devices.…”
mentioning
confidence: 99%